2012
DOI: 10.1126/scitranslmed.3003807
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Glycosides Exert Anticancer Effects by Inducing Immunogenic Cell Death

Abstract: Some successful chemotherapeutics, notably anthracyclines and oxaliplatin, induce a type of cell stress and death that is immunogenic, hence converting the patient's dying cancer cells into a vaccine that stimulates antitumor immune responses. By means of a fluorescence microscopy platform that allows for the automated detection of the biochemical hallmarks of such a peculiar cell death modality, we identified cardiac glycosides (CGs) as exceptionally efficient inducers of immunogenic cell death, an effect tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
341
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 370 publications
(354 citation statements)
references
References 35 publications
13
341
0
Order By: Relevance
“…U2OS cells stably co-expressing GFP-LC3 or HMGB1-GFP 56 were maintained under 200 mg/ml G418 selective pressure. U2OS cells engineered for the stable expression of a CRT-GFP fusion 17 were cultured in the continuous presence of 100 mg/ml zeocin. Control (SCR), Atg5 KD and Atg7 KD MCA205 cells 23 were maintained under 5 mg/ml puromycin selection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…U2OS cells stably co-expressing GFP-LC3 or HMGB1-GFP 56 were maintained under 200 mg/ml G418 selective pressure. U2OS cells engineered for the stable expression of a CRT-GFP fusion 17 were cultured in the continuous presence of 100 mg/ml zeocin. Control (SCR), Atg5 KD and Atg7 KD MCA205 cells 23 were maintained under 5 mg/ml puromycin selection.…”
Section: Methodsmentioning
confidence: 99%
“…2,3,13 Of note, most inducers of apoptosis and necrosis fail to trigger ICD. However, a few chemotherapeutics, including anthracyclines, 7,8 OXA, 14 cyclophosphamide, 15 and -to some extent -microtubular inhibitors, 16 as well as cardiac glycosides, [17][18][19] potently do so. 20,21 Such chemicals appear to be particularly efficient at inducing a pre-mortem endoplasmic reticulum (ER) stress response and autophagy.…”
mentioning
confidence: 99%
“…It has been recently proposed that they can be classified into two categories, type I or II ICD inducers, based on their distinct actions to induce ER stress leading to apoptotic cell death (Tables 2 and 3). 27,28 The majority of ICD inducers such as chemotherapeutic agents (mitoxantrone, 29 anthracyclines, 2,30,31 oxaliplatin, 18,19 and cyclophosphamide 32 ), shikonin, 33,34 the proteasome inhibitor bortezomib, 35 and 7A7 (an epidermal growth factor receptor-specific antibody), 36 cardiac glycosides, 37 and the histone deacetylase inhibitor (vorinostat) 38 are categorized as type I ICD inducers that primarily target cytosolic proteins, plasma membranes, or nucleic proteins. They also induce ER stress via collateral effects.…”
Section: Icd Inducersmentioning
confidence: 99%
“…48 The ecto-CRT induction capacity of ICD inducers has been shown to depend on the properties of ER stress and ROS production. 2,37,49 Cancer cells can induce ecto-CRT followed by disturbance of the ER structure with GADD34 activation and PERK phosphorylation. It has been shown that depletion of PERK abolishes anthracycline-driven ecto-CRT and immunogenicity of cellular death (ER stress module), 19 and that caspase-8 acts upstream of apoptotic proteins Bax and Bak, and subsequent cleavage of its substrate Bap31 (apoptotic module) is indispensable for ecto-CRT induction.…”
Section: Calreticulin Exposurementioning
confidence: 99%
“…16 In line with this notion, lethal stimuli that fail to elicit sufficient degrees of ER stress (such as mitomycin C and cisplatin) cannot induce the immunogenic exposure of CRT on the cell surface, unless an exogenous source of ER stress is provided. 13,17,18 In contrast, anthracyclines and oxaliplatin are highly efficient at stimulating the PERK-mediated phosphorylation of eIF2a, followed by the caspase-8-mediated cleavage of BCAP31, BAX/BAK activation (presumably at the ER membrane), the anterograde transport of CRT-containing vesicles from the ER to the cell surface (via the Golgi apparatus), and -eventually -the SNAP receptor (SNARE)-dependent fusion of such vesicles with the plasma membrane. 5,16 In response to some (but not all) ICD inducers, protein disulfide isomerase family A, member 3 (PDIA3), an ER reticulum chaperone best known as ERp57, is required for the translocation of (and de facto physically escorts) CRT to the outer leaflet of the plasma membrane.…”
mentioning
confidence: 99%